A kind of hexagonal boron nitride nanosheet and preparation method thereof
The conversion of micron-scale boron nitride into high-concentration hexagonal boron nitride nanosheets through mechanical shear peeling and peeling methods has solved the problem of difficulty in achieving high concentration and high efficiency production in the prior art, achieved low-cost, green and environmentally friendly nanosheet preparation, and promoted its wide application in many fields.
Patent Information
- Application Number
- CN202411974083.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to achieve high concentration, high efficiency and large-scale production of hexagonal boron nitride nanosheets, and the peeling process is complex and the cost is high, which limits its wide application.
Mechanical shear stripping was obtained by adding micron-scale boron nitride and an acid solvent to the dispersant to obtain a high concentration of boron nitride nano paste, and hexagonal boron nitride nanosheets were obtained by washing and drying steps. This method does not require pretreatment of boron nitride, and the chemical additives used are not contaminated, making it suitable for industrial production.
The high concentration (thickness <20 nm), high yield and high efficiency preparation of hexagonal boron nitride nanosheets was achieved, which reduced the use of acid solvents and production costs, and promoted the use of boron nitride in practical applications.
Smart Images

Figure CN119735173A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material preparation, and in particular to a hexagonal boron nitride nano sheet and a preparation method thereof. Background Art
[0002] Hexagonal Boron Nitride (h-BN) is a material with a unique two-dimensional layered structure. Due to the strong covalent bonds of BN within the layer and the weak van der Waals forces between the layers, it is possible to peel off single-layer or few-layer hexagonal boron nitride nanosheets (BNNSs) from h-BN. BNNSs have high thermal conductivity, good insulation, excellent mechanical strength and chemical stability, and show great application potential in many fields such as electronic devices, composite materials, catalyst carriers, and energy storage and conversion.
[0003] Despite the promising application prospects of BNNSs, the large-scale, high-efficiency and low-cost preparation technology has always been the key bottleneck restricting its application. Early studies successfully exfoliated BNNSs from h-BN by micromechanical cleavage, thus verifying the feasibility of exfoliation. However, the yield of this method is extremely low, which is limited to the preparation of small amounts of samples for basic research and cannot meet the needs of large-scale applications. To overcome this limitation, researchers subsequently turned to solution-based exfoliation strategies, using mechanical equipment such as ultrasound, high-shear mixers, high-pressure homogenizers or planetary ball mills, adding auxiliary exfoliants (such as strong acids, strong bases, intercalation agents or surfactants) to solvents (including single-component solvents or mixed solvents), and optimizing processing conditions (such as increasing temperature, shock cooling or increasing pressure) to increase the yield and dispersion concentration of BNNSs. Although these methods have improved the yield of BNNSs to a certain extent, the concentration of the resulting BNNSs dispersion is usually still less than 1 mg / ml, and the yield is also less than 30%, indicating that most h-BN particles are not completely stratified and still exist in the form of thick flakes.
[0004] In recent years, some studies have begun to focus on solid-based exfoliation strategies, such as direct treatment of commercial h-BN using high-energy mechanochemical ball milling. This method breaks and delaminates h-BN particles through intense impact and friction applied by heavy balls and mechanochemical reactions, resulting in high yield and well-dispersed BNNSs. However, these methods usually require complex post-processing steps such as centrifugation, washing or dialysis to remove unexfoliated h-BN particles and excess active chemicals, which not only increases the complexity and cost of the production process, but also limits the large-scale application of BNNSs. In addition, from the perspective of practical production, existing BNNSs exfoliation methods often find it difficult to achieve full conversion, high concentration, high efficiency and high yield production. Low-concentration BNNSs dispersions are only suitable for dilute solution-based processing methods such as filtration or evaporation, which are time-consuming, labor-intensive, and have limited scalability, and are heavily dependent on the size and shape of the substrate. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing hexagonal boron nitride nanosheets, which is used to solve the problem that the BNNSs exfoliation method in the prior art is difficult to achieve full conversion and high concentration production.
[0006] The present invention also provides a hexagonal boron nitride nanosheet to solve the problem of low concentration of hexagonal boron nitride nanosheets prepared by the BNNSs stripping method in the prior art.
[0007] In order to solve the above problems, the present invention proposes a method for preparing hexagonal boron nitride nanosheets, and the technical solution adopted is: A method for preparing hexagonal boron nitride nanosheets comprises the following steps: adding micron-sized boron nitride and an acid solvent into a dispersant for mechanical shearing and exfoliation to obtain a high-concentration boron nitride nanopaste; and washing and drying the high-concentration boron nitride nanopaste to obtain hexagonal boron nitride nanosheets.
[0008] The beneficial effects of the present invention are: 1) The preparation method of hexagonal boron nitride nanosheets of the present invention does not require pretreatment of boron nitride; the added acid solvent can protonate the boron nitride, and the local disturbance of the protons can form a positively charged part. The charge generates a repulsive force between the boron nitride layers, causing the spacing between the boron nitride to increase and facilitate peeling; and when the polarity of the added acid solvent matches the surface energy of h-BN, the acid solvent molecules can form a tight arrangement on the h-BN surface and produce a strong interaction. This interaction helps to weaken the interaction force between the h-BN layers, thereby reducing the peeling energy, resulting in a loose structure that reduces the difficulty of peeling; mechanical shear peeling causes the layers of the nanosheets to separate, and obtain large-sized BNNSs. The preparation method of the present invention is green and environmentally friendly, and the chemical additives used are pollution-free, which is convenient for industrial production; 2) The high-concentration boron nitride nanopaste prepared by the present invention has a corresponding nanosheet thickness of less than 20 nm and a lateral size of micrometer level. The dispersant has excellent dispersibility and can be diluted and used in any proportion. The dispersion system and concentration can be customized according to customer needs; 3) The high-concentration boron nitride nanopaste prepared by the present invention has the characteristics of ultra-high concentration, high yield, high stability, etc., reduces the use of acid solvents, reduces costs, and promotes the application of boron nitride in practice; 4) The preparation method of the present invention is simple to operate, does not require pretreatment of boron nitride, and can achieve large-scale, high-efficiency, low-cost macro-quantity preparation of hexagonal boron nitride nanosheets.
[0009] In order to further increase the spacing between boron nitride and facilitate stripping, preferably, the mass ratio of the micron-sized boron nitride to the acid solvent is 60: (1-1.5).
[0010] In order to improve the protonation of boron nitride and reduce the difficulty of boron nitride stripping, preferably, the acid solvent is one of oxalic acid, carbonic acid, sulfuric acid and organic acid.
[0011] In order to further improve the effect of mechanical shearing and peeling, preferably, the stirring speed of the mechanical shearing and peeling is 2000-8000 rpm, and the time is 1-500 hours.
[0012] In order to fully disperse the micron-sized boron nitride and the acid solvent, preferably, the dispersant is one or more of water, ethanol, nitrogen methyl pyrrolidone, N-dodecyl pyrrolidone, pyridine dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, N-vinyl pyrrolidone, dimethyl imidazolone, N-methylformamide, dimethylformamide, isopropanol, etc.
[0013] In order to further improve the dispersibility of micron-sized boron nitride and facilitate stripping, preferably, the volume ratio of the mass of the micron-sized boron nitride to the dispersant is (1-1.3):4.
[0014] Preferably, the drying temperature is 100-110° C. and the drying time is 6-7 hours.
[0015] In order to achieve efficient and high-concentration exfoliation of BNNSs, preferably, the step of adding micron-sized boron nitride and an acid solvent into a dispersant for mechanical shear exfoliation to obtain a high-concentration boron nitride nanopaste specifically includes: Micron-sized boron nitride and an acid solvent are added to a dispersant, and mechanical shearing and exfoliation are performed in a grinding device using balls, rods or segments as the medium, so that a high-concentration boron nitride nanopaste is prepared in a one-step method.
[0016] Preferably, the types of balls, rods or segments are one or more of iron oxide balls, steel balls, steel rods, copper oxide balls, zirconium oxide balls, aluminum oxide balls, alloy rods, iron oxide rods, copper oxide rods, zirconium oxide rods, aluminum oxide rods, steel segments, alloy segments, copper oxide segments, aluminum oxide segments, gravel, pebbles, porcelain balls, agate balls, alloy balls, iron oxide segments, and zirconium oxide segments.
[0017] The present invention also proposes a hexagonal boron nitride nanosheet, and the technical solution adopted is: A hexagonal boron nitride nanosheet is prepared by the above-mentioned method for preparing the hexagonal boron nitride nanosheet.
[0018] The beneficial effects of the present invention are as follows: the thickness of the hexagonal boron nitride nanosheet of the present invention is less than 20 nm, the lateral size is micrometer level, it has excellent physical and chemical properties, and shows wide application potential in many fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a physical picture of the hexagonal boron nitride nano-paste prepared in Example 1 of the method for preparing hexagonal boron nitride nano-sheets of the present invention; Figure 2 The XRD spectrum of the hexagonal boron nitride nanosheets prepared in Example 1 of the method for preparing hexagonal boron nitride nanosheets of the present invention; Figure 3 This is a SEM image of the micron-sized boron nitride raw material used in the method for preparing hexagonal boron nitride nanosheets of the present invention; Figure 4 This is a SEM image of the hexagonal boron nitride nanopaste prepared in Example 1 of the method for preparing hexagonal boron nitride nanosheets of the present invention; Figure 5 This is a SEM image of the hexagonal boron nitride nanopaste prepared in Example 2 of the method for preparing hexagonal boron nitride nanosheets of the present invention; Figure 6 This is a TEM image of the hexagonal boron nitride nanopaste prepared in Example 1 of the method for preparing hexagonal boron nitride nanosheets of the present invention; Figure 7 This is a TEM image of the hexagonal boron nitride nanopaste prepared in Example 2 of the method for preparing hexagonal boron nitride nanosheets of the present invention; Figure 8 This is a TEM image of the edge of the hexagonal boron nitride nanosheet prepared in Example 1 of the method for preparing the hexagonal boron nitride nanosheet of the present invention. DETAILED DESCRIPTION
[0020] The BNNSs exfoliation method in the prior art is difficult to achieve full conversion and high-concentration production. The present invention provides a method for preparing hexagonal boron nitride nanosheets, comprising the following steps: adding micron-sized boron nitride and an acid solvent to a dispersant for mechanical shear exfoliation to obtain a high-concentration boron nitride nanopaste; washing and drying the high-concentration boron nitride nanopaste to obtain hexagonal boron nitride nanosheets.
[0021] The technical concept of the present invention is: the acid solvent can protonate boron nitride, and the local disturbance of the proton can form a positively charged part. The charge generates a repulsive force between the boron nitride layers, causing the spacing between the boron nitride to increase and facilitate peeling; and when the polarity of the added acid solvent matches the surface energy of h-BN, the acid solvent molecules can form a close arrangement on the h-BN surface and produce a strong interaction. This interaction helps to weaken the interaction force between the h-BN layers, thereby reducing the peeling energy, resulting in a loose structure that reduces the difficulty of peeling; mechanical shear peeling causes the layers of the nanosheets to separate, and obtain large-sized BNNSs. The dispersant has excellent dispersibility and can be diluted and used in any proportion. The dispersion system and concentration can be customized according to customer needs. The boron nitride nanopaste prepared by the present invention has the characteristics of ultra-high concentration, high yield, high stability, etc., reduces the use of acid solvents, reduces costs, and promotes the application of boron nitride in practice. The preparation method of the present invention is green and environmentally friendly, and the chemical additives used are pollution-free and convenient for industrial production.
[0022] Specifically, the preparation method of hexagonal boron nitride nanosheets comprises the following steps: First, micron-sized boron nitride is added to the jar; Secondly, adding the acid solvent into the aqueous dispersion and stirring to completely dissolve the acid solvent to obtain a mixed solution; Next, the mixed solution is added to the above-mentioned jar, and a grinding device with balls as the medium is added to the jar for mechanical shearing and exfoliation, so as to prepare a high-concentration boron nitride nanopaste in one step; wherein the stirring speed of the mechanical shearing and exfoliation is 2000-8000 rpm, and the time is 1-500 hours; Finally, the high-concentration boron nitride nanopaste is washed and dried to obtain hexagonal boron nitride nanosheets; wherein the drying temperature is 100-110° C. and the drying time is 12-13 hours.
[0023] Preferably, the mass ratio of micron-sized boron nitride to acid solvent is 60:(1-1.5).
[0024] Preferably, the mass ratio of micron-sized boron nitride to the volume ratio of the dispersant is (1-1.3):4.
[0025] Preferably, the micron-sized boron nitride may be in block or powder form, and there is no specific requirement for the form of the boron nitride.
[0026] Preferably, the grinding equipment using balls, rods or segments as the medium is one or more of a high-speed shearing machine, a ball mill, a pebble mill, a sand mill, a shearing homogenizer, wherein the diameter of the balls is 0.005 mm to 150 mm.
[0027] The implementation process of the present invention is described in detail below in conjunction with specific embodiments. However, it will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. It should also be noted that, for ease of description, only the parts related to the invention are shown in the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail with reference to the embodiments below. It should be noted that the endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.
[0028] In the following examples, the raw materials used are all common commercial products that can be directly purchased or can be prepared according to conventional techniques in the art.
[0029] 1. Specific embodiment of the method for preparing hexagonal boron nitride nanosheets of the present invention Example 1 The method for preparing hexagonal boron nitride nanosheets provided in this embodiment comprises the following steps: First, add 60 g of micron-sized boron nitride into a 500 mL jar; Secondly, 1 g of oxalic acid is added into 240 ml of aqueous dispersion and stirred to completely dissolve the oxalic acid to obtain a mixed solution; wherein the aqueous dispersion includes water and nitrogen methyl pyrrolidone.
[0030] Next, the mixed solution was added to the above jar, and a grinding device with balls as the medium was added to the jar for mechanical shearing and exfoliation, and a high concentration of 201 mg / ml boron nitride nanopaste was prepared in one step, as shown in FIG. Figure 1 As shown; wherein, the stirring speed of mechanical shear peeling is 2000rmp, the time is 24h; the diameter of the ball is 150mm; Finally, the high-concentration boron nitride nanopaste is washed and dried to obtain hexagonal boron nitride nanosheets; wherein the drying temperature is 100° C. and the drying time is 6 hours.
[0031] Example 2 The method for preparing hexagonal boron nitride nanosheets provided in this embodiment comprises the following steps: First, add 120 g of micron-sized boron nitride into a 1000 mL jar; Secondly, 2 g of oxalic acid was added into 480 ml of the aqueous dispersion and stirred to completely dissolve the oxalic acid to obtain a mixed solution; wherein the aqueous dispersion comprises water and N-dodecylpyrrolidone.
[0032] Next, the mixed solution was added to the above jar, and a grinding device with a rod as the medium was added to the jar for mechanical shearing and exfoliation, and a high concentration of 189 mg / ml boron nitride nanopaste was prepared in one step, as shown in FIG. Figure 2 As shown; wherein, the stirring speed of mechanical shear peeling is 8000rmp, and the time is 500h; Finally, the high-concentration boron nitride nanopaste is washed and dried to obtain hexagonal boron nitride nanosheets; wherein the drying temperature is 100° C. and the drying time is 7 hours.
[0033] In the present application, when the mass ratio of micron-sized boron nitride to acid solvent is 60:1.5, the technical effects of the prepared high-concentration boron nitride nanopaste and hexagonal boron nitride nanosheets are the same as those of the above-mentioned embodiments.
[0034] In the present application, when the mass ratio of micron-sized boron nitride to the volume ratio of the dispersant is 1.3:4, the technical effects of the prepared high-concentration boron nitride nanopaste and hexagonal boron nitride nanosheets are the same as those of the above-mentioned embodiments.
[0035] In the present application, when the acid solvent is one of carbonic acid, sulfuric acid and organic acid, the technical effects of the prepared high-concentration boron nitride nanopaste and hexagonal boron nitride nanosheets are the same as those of the above embodiments.
[0036] 2. Experimental Examples Experimental Example 1 The hexagonal boron nitride nanosheets and micron-sized boron nitride prepared in Example 1 were characterized by XRD. The test results are as follows: Figure 2 As shown. It can be seen that by comparing the crystal structures of hexagonal boron nitride nanosheets and micron-sized boron nitride, the structure of BNNSs remains unchanged during the surface liquid phase exfoliation process and does not contain additional impurities. The high intensity diffraction peak at 25-30° proves the high crystallinity of the exfoliated hBNNS, indicating that there are fewer defects in the hexagonal boron nitride nanosheets.
[0037] Experimental Example 2 The high concentration boron nitride nanopaste prepared in the above examples 1-2 was subjected to SEM and TEM detection. Specifically, the high concentration boron nitride nanopaste prepared in the above examples 1-2 was diluted and detected using a scanning electron microscope and a transmission electron microscope. The obtained SEM images are shown in Figures 4 and 5. Figure 5 As shown in TEM images 6 and Figure 7 At the same time, the SEM image of the micron-sized boron nitride raw material used in the embodiment is as shown Figure 3 It can be seen that there is obvious exfoliated boron nitride in the high concentration boron nitride nanopaste prepared in Example 1-2, and the thickness of the exfoliated boron nitride is significantly reduced.
[0038] The edge morphology of the hexagonal boron nitride nanosheets prepared in Example 1 was detected. Specifically, a transmission electron microscope was used to detect the edge morphology of the hexagonal boron nitride nanosheets, and a TEM image of the edge morphology of the hexagonal boron nitride nanosheets was obtained. Figure 8 As shown, it can be seen that the thickness of a single layer of hexagonal boron nitride nanosheet is about 0.34 nm, and the lateral size is micrometer-level, indicating that the preparation method of the present application successfully prepares hexagonal boron nitride nanosheets.
[0039] It can be seen that the hexagonal boron nitride nanosheets prepared by the preparation method of the hexagonal boron nitride nanosheets provided by the present application have the characteristics of ultra-high concentration, high yield, high stability, etc., which reduces the use of acid solvents, reduces costs, and promotes the application of boron nitride in practice. The preparation method of the present invention is green and environmentally friendly, and the chemical additives used are pollution-free, which is convenient for industrial production.
[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing hexagonal boron nitride nanosheets, characterized in that: The following steps are involved: Micron-sized boron nitride and an acid solvent are added to a dispersant for mechanical shearing and exfoliation to obtain a high-concentration boron nitride nanopaste; the high-concentration boron nitride nanopaste is washed and dried to obtain hexagonal boron nitride nanosheets.
2. The method for preparing hexagonal boron nitride nanosheets according to claim 1, characterized in that: The mass ratio of the micron-sized boron nitride to the acid solvent is 60:(1-1.5).
3. The method for preparing hexagonal boron nitride nanosheets according to claim 2, characterized in that: The acid solvent is one of oxalic acid, carbonic acid, sulfuric acid and organic acid.
4. The method for preparing hexagonal boron nitride nanosheets according to claim 1, characterized in that: The stirring speed of the mechanical shearing peeling is 2000-8000 rpm, and the time is 1-500 hours.
5. The method for preparing hexagonal boron nitride nanosheets according to claim 1, characterized in that: The dispersant is one or more of water, ethanol, nitrogen methyl pyrrolidone, N-dodecyl pyrrolidone, pyridine dimethylformamide, dimethyl sulfoxide, tetrahydrofuran, N-vinyl pyrrolidone, dimethyl imidazolone, N-methylformamide, dimethylformamide, and isopropanol.
6. The method for preparing hexagonal boron nitride nanosheets according to claim 5, characterized in that: The mass ratio of the micron-sized boron nitride to the volume ratio of the dispersant is (1-1.3):
4.
7. The method for preparing hexagonal boron nitride nanosheets according to claim 1, characterized in that: The drying temperature is 100-110° C. and the drying time is 6-7 hours.
8. The method for preparing hexagonal boron nitride nanosheets according to claim 1, characterized in that: The step of adding micron-sized boron nitride and an acid solvent into a dispersant for mechanical shearing and exfoliation to obtain a high-concentration boron nitride nanopaste specifically includes: Micron-sized boron nitride and an acid solvent are added to a dispersant, and mechanical shearing and exfoliation are performed in a grinding device using balls, rods or segments as the medium, so that a high-concentration boron nitride nanopaste is prepared in a one-step method.
9. The method for preparing hexagonal boron nitride nanosheets according to claim 8, characterized in that: The types of balls, rods or segments are one or more of iron oxide balls, steel balls, steel rods, copper oxide balls, zirconium oxide balls, aluminum oxide balls, alloy rods, iron oxide rods, copper oxide rods, zirconium oxide rods, aluminum oxide rods, steel segments, alloy segments, copper oxide segments, aluminum oxide segments, gravel, pebbles, porcelain balls, agate balls, alloy balls, iron oxide segments, and zirconium oxide segments.
10. A hexagonal boron nitride nanosheet, characterized in that: The hexagonal boron nitride nanosheet is prepared by the preparation method of any one of claims 1 to 9.